Physico-chemical properties of reduced-fat biscuits prepared using O/W cellulose-based pickering emulsion. (August 2021) - Xie, Yunxiao; Lei, Yujie; Rong, Jianhua; Zhang, Xingzhong; Li, Jing; Chen, Yijie; Liang, Hongshan; Li, Yan; Li, Bin; Fang, Zhicai; Luo, Xiaogang; Pei, Ying; et al.
Abstract: This study was aimed at evaluating the potential of oil-in-water (O/W) Pickering emulsions stabilized with dietary fibers as fat substitutes to prepare low-calorie baked foods. The chewy biscuits were used as a research model to evaluate the feasibility of Pickering emulsions with different oil phase volume fractions (10%–50%) as fat substitutes. The dough mixing characteristics and biscuit quality with different fat replacement rates (0%–90%) were assessed. The bacterial cellulose (BC) and bamboo shoot water-insoluble dietary fiber (BSDF) were used to provide good stabilization of O/W emulsions against coalescence over a period of one month. In the reduced-fat doughs, dietary fiber increased the viscoelasticity of the dough by altering the gluten network structure and forming a discontinuous, irregular matrix. The overall appearance and texture of the biscuits were better when the fat replacement rate was 35%. Moreover, the reduced fat energy was 12.5 kJ/g, and the amount of dietary fiber increased to 1.05 mg/g. The fingdings might expand the potential application of Pickering emulsion stabilized with dietary fibers as fat substitutes in the development of low-fat baked foods. Highlights: The O/W Pickering emulsions were stabilized by using dietary fiber. Dietary fiber induced changes in gluten network structure and rheology of dough. Pickering emulsion could be used as a fat substitute for low-calorie baked foods.